2019
DOI: 10.1152/ajpcell.00072.2019
|View full text |Cite
|
Sign up to set email alerts
|

GABA receptors differentially regulate life span and health span in C. elegans through distinct downstream mechanisms

Abstract: GABA, a prominent inhibitory neurotransmitter, is best known to regulate neuronal functions in the nervous system. However, much less is known about the role of GABA signaling in other physiological processes. Interestingly, recent work showed that GABA signaling can regulate life span via a metabotropic GABAB receptor in Caenorhabditis elegans. However, the role of other types of GABA receptors in life span has not been clearly defined. It is also unclear whether GABA signaling regulates health span. Here, us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 53 publications
2
19
0
Order By: Relevance
“…Previously, we also found that AgNPs coated with PVP could cause more severe oxidative stress and subacute toxicity at the same dose in mice compared with noncoated nanoparticles (Gan et al, 2020). Consistent with those findings, in the current study, we observed that both kinds of AgNPs induced a significant decrease in the survival rate of C. elegans (≥1 mg·L −1 ) either in 48 h or 6 days in a time‐ and dose‐dependent manner; nevertheless, PVP‐AgNPs caused more evident life losses, because the lifespan of C. elegans has complex regulatory mechanisms and GABAergic neurons are involved (Yuan et al, 2019). The study of the effects of AgNPs on the longevity of nematodes can help us better understand the long‐term toxicity and biological toxicity of AgNPs (Bayersdorf & Schumacher, 2019).…”
Section: Discussionsupporting
confidence: 90%
“…Previously, we also found that AgNPs coated with PVP could cause more severe oxidative stress and subacute toxicity at the same dose in mice compared with noncoated nanoparticles (Gan et al, 2020). Consistent with those findings, in the current study, we observed that both kinds of AgNPs induced a significant decrease in the survival rate of C. elegans (≥1 mg·L −1 ) either in 48 h or 6 days in a time‐ and dose‐dependent manner; nevertheless, PVP‐AgNPs caused more evident life losses, because the lifespan of C. elegans has complex regulatory mechanisms and GABAergic neurons are involved (Yuan et al, 2019). The study of the effects of AgNPs on the longevity of nematodes can help us better understand the long‐term toxicity and biological toxicity of AgNPs (Bayersdorf & Schumacher, 2019).…”
Section: Discussionsupporting
confidence: 90%
“…The UNC-30 pathway also controls genes that are involved in aging (Apfeld andKenyon, 1999, 2004;Jeong et al, 2012;Kenyon, 2010;Wolkow et al, 2000). The G proteincoupled GABA receptor GBB-1 modulates longevity through G protein-PLCb, which transmits longevity signals to FOXO/DAF-16 (Chun et al, 2015;Yuan et al, 2019). Our studies highlight a role for neural UNC-30 in the integration of signals that control the balance between the activation of both immune and longevity pathways that have opposite effects.…”
Section: Figure 6 Asg Neurons Control the Immunity-longevity Tradeoffmentioning
confidence: 78%
“…However, the structure of GABA B – G i1 complex coupling via GB1 demonstrates that GB1 couples to G i protein at certain circumstance. Indeed, GB1 in C. elegans directly couples to G i/o protein-dependent signaling 47,48 , indicating that GB1 retains the capacity for Gi protein coupling during evolution. Common activation mechanism for G protein activation by GPCRs has been proposed, in which the landmark of GPCR activation is the outwards movement of TM6 forming a cavity to accommodate the G proteins or β-arrestins, reflecting the convergence of activation pathways in class A, B and F GPCRs 43,49,50 .…”
Section: Resultsmentioning
confidence: 99%